The Construction of Public Trust in AI-Based Information in Digital Media: An Analysis of Audience Perception and Communication Literacy - Mufid Mufid (PT. AVID MEDIA INDONESIA, 2025)
This study examines the construction of public trust in artificial intelligence (AI)-based information in digital media through a qualitative approach in the form of a literature review. The study focuses on three main aspects: the mechanism of public trust formation in AI content, the role of audience communication literacy in interpreting and assessing message credibility, and the impact of trust-literacy interactions on the dynamics of contemporary digital communication. Literature findings indicate that audience perceptions of the credibility of AI information are influenced by technological factors, previous media experience, and communication literacy levels, which collectively form a dynamic and heterogeneous trust structure. Communication literacy has been shown to be an important mediator in strengthening audiences' ability to evaluate and verify information, thereby reducing vulnerability to misinformation. The implications of this study emphasize that strengthening communication literacy and transparency in the use of AI by the media are prerequisites for the formation of rational and sustainable trust. The study's conclusions provide conceptual contributions to the development of ethical digital communication strategies and audience capacity building in the AI ​​era.